Direct Interaction between the WD40 Repeat Protein WDR-23 and SKN-1/Nrf Inhibits Binding to Target DNA - Leung, Chi K. (American Society for Microbiology, 2014)
SKN-1/Nrf transcription factors activate cytoprotective genes in response to reactive small molecules and strongly influence stress resistance, longevity, and development. The molecular mechanisms of SKN-1/Nrf regulation are poorly defined. We previously identified the WD40 repeat protein WDR-23 as a repressor of Caenorhabditis elegans SKN-1 that functions with a ubiquitin ligase to presumably target the factor for degradation. However, SKN-1 activity and nuclear accumulation are not always correlated, suggesting that there could be additional regulatory mechanisms. Here, we integrate forward genetics and biochemistry to gain insights into how WDR-23 interacts with and regulates SKN-1. We provide evidence that WDR-23 preferentially regulates one of three SKN-1 variants through a direct interaction that is required for normal stress resistance and development. Homology modeling predicts that WDR-23 folds into a β-propeller, and we identify the top of this structure and four motifs at the termini of SKN-1c as essential for the interaction. Two of these SKN-1 motifs are highly conserved in human Nrf1 and Nrf2 and two directly interact with target DNA. Lastly, we demonstrate that WDR-23 can block the ability of SKN-1c to interact with DNA sequences of target promoters identifying a new mechanism of regulation that is independent of the ubiquitin proteasome system, which can become occupied with damaged proteins during stress.